222 COVID-19 Related Stress Intensify the Impact of Child Maltreatment on Sleep Quality. (3rd May 2021) - Zhang, Linhao; Cui, Zehua; Sasser, Jeri; Oshri, Assaf
Abstract: Introduction: Child maltreatment (CM) is a significant stressor that is associated with sleep problems in children and adolescents. The COVID-19 pandemic introduces new psychosocial stressors, which may be particularly harmful to youth already experiencing stress in the home environment. Using multi-dimensional (threat vs deprivation) assessments of CM, the present study aimed to test whether COVID-19 related stress intensified the association between maltreatment (abuse vs neglect) and sleep problems among youth. Methods: This study utilized data from a longitudinal sample of youth (N=126; Mage at T1=12.9) assessed between January 2019 and March 2020 (T1) and after the beginning of the COVID-19 pandemic (May 2020; T2). Latent factors for COVID-19 related stress included three questions asking about negative changes, uncertainty about the future, and stress-induced by disruptions. CM at T1 was measured with the Childhood Trauma Questionnaire (CTQ). Multidimensional aspects of CM included a threat factor (sum of Emotional, Physical, and Sexual Abuse) and a deprivation factor (sum of Emotional and Physical Neglect). Sleep-related problems at both T1 and T2 were assessed using the Pittsburgh Sleep Quality Index (PSQI) global score. Structural equation modeling was conducted in Mplus 8.1 to test direct and interaction effects of CM and COVID-19 related stress on sleep problems at T2 while controlling for sleep problems at T1 and demographic covariates. Results: Threat-related abuse was significantly associated with increased sleep problems at T2 (β =.43, p < .01) but neglect was not (β =.03, p = .85). Additionally, COVID-19 related stress significantly intensified the link between abuse and sleep problems (β =.14, p < .05) as well as between neglect and sleep problems (β =.43, p < .01) at T2. Among youth who experienced higher levels of CM, increased COVID-19 related stress exacerbated sleep problems. Conclusion: These results bolster extant research on the negative impact CM bears on youth sleep health and indicates that COVID-19 stress may exacerbate sleep problems. Our findings inform future prevention and intervention efforts that aim to reduce sleep problems among youth who experience CM during the COVID-19 pandemic. Support (if any): NIH/NIDA K Grant 1K01DA045219-01